Pengaruh Fasilitas Kerja dan Lingkungan Kerja Non Fisik Terhadap Kinerja Pegawai Dinas Perhubungan Kabupaten Tasikmalaya - Fany Sucyana Putri; Arga Sutrisna; Ai Kusmiati Asyiah (Jurnal Publikasi Ilmu Manajemen, 2023)
This study aims to determine the Effect of Work Facilities and Non-Physical Work Environment on the Performance of Employees of the Tasikmalaya District Transportation Office. This study uses a causality quantitative method. The type of data used is primary data and secondary data, with a sample of 87 respondents from the Tasikmalaya District Transportation Office employees, and using the saturated sample method. The data analysis tool used in this study was SPSS Version 25. Data collection techniques used observation, interviews, questionnaires, and literature studies. The results of the study show that the Work Facilities and Non-Physical Work Environment simultaneously have a significant effect on Employee Performance. Work facilities partially have a significant effect on employee performance. Non-Physical Work Environment partially has a significant effect on Employee Performance.